Кераміка середини ХІІІ ст. з садиби ювеліра в Любечі - Веремейчик, О.М. (Археологія і давня історія України, 2018)
Стаття присвячена характеристиці керамічного матеріалу з садиби ювеліра, дослідженої у
2010—2011 рр. на городищі Замкова Гора у Любечі.
Вона складалась з шести споруд різного призначення, у тому числі і житлової, які загинули у пожежі середини ХІІІ ст. У всіх об'єктах садиби виявлений численний керамічний матеріал, у тому числі і цілі посудини. Серед керамічного посуду зустрінуті фрагменти з поливою. The article is devoted to the description of ceramic
material from the jeweler’s estate investigated in
2010—2011 on the site Zamkova Gora in Lyubech. The
estate consisted of six buildings for various purposes, including residential which had been destroyed by fire
in the middle of the 13th century. In all objects of the estate, there were numerous ceramic materials, including
whole jugs. Among the ceramic dishes are found fragments with glaze.
The assortment of discovered vessels includes kitchenware, dining, and tare. The kitchenware represented
by pots, the dining — by bowls, mugs, jugs and decorative plates, tare — by korchagas.